THE IMPORTANCE OF CLT METHOD IN TEACHING ENGLISH LANGUAGE - Tungatarova Madina (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The article studies the potential of the Communicative Language Teaching (CLT) activities to develop learners’ foreign language skills and knowledge. The language teaching methods and approaches are the most crusial way to learning effectively new language. CLT is becoming a major language and its being used worldwide. Communicative Language Teaching (CLT) is also called the communicative approach, which focuses on teaching a foreign or second language through communication and interaction. This approach looks at communication as a method for English language learners (ELLs), who are students whose first language is not English.